Conflict and confrontation in South East Asia, 1961-1965 : Britain, the United States, and the creation of Malaysia - Matthew, Jones (Cambridge University, 2013)
In the early 1960s, Britain and the United States were still trying to come to terms with the powerful forces of indigenous nationalism unleashed by the Second World War. The Indonesia-Malaysia confrontation--a crisis which was, as Macmillan remarked to Kennedy, 'as dangerous a situation in South East Asia as we have seen since the war'--was a complex test of Anglo-American relations. As American commitment to Vietnam accelerated under the Kennedy and Johnson Administrations, Britain was involving herself in an 'end-of-empire' exercise in statebuilding which had important military and political implications for both nations. Matthew Jones provides a detailed insight into the origins, outbreak and development of this important episode in international history; using a large range of previously unavailable archival sources, he illuminates the formation of the Malaysian federation, Indonesia's violent opposition to the new state and the Western powers' attempts to deal with the resulting conflict.